2022
DOI: 10.1007/s00192-022-05302-6
|View full text |Cite
|
Sign up to set email alerts
|

Elite female athletes’ experiences of symptoms of pelvic floor dysfunction: A systematic review

Abstract: Introduction and aims Pelvic floor dysfunction (PFD) is a collection of signs, symptoms and conditions affecting the pelvic floor and urinary incontinence (UI) is the most common type of PFD. Recent systematic reviews have indicated a higher prevalence of UI among female athletes compared to their non-athletic counterparts. To date, no review has been undertaken to investigate female athletes’ experiences of PFD. This review aims to offer insight and understanding, through aggregation, summary, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Community dwelling women report that living with UI evokes feelings of shame and humiliation; they are concerned that others will notice their symptoms in social settings and judge them unfavourably [ 46 ]. The current study builds on knowledge obtained from prior survey data that female athletes report embarrassment, fear, anxiety and frustration as a consequence of PF disorders [ 20 ]. Many of the same negative emotions were also reported by participants within our study and the basis for experiencing these emotions described.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Community dwelling women report that living with UI evokes feelings of shame and humiliation; they are concerned that others will notice their symptoms in social settings and judge them unfavourably [ 46 ]. The current study builds on knowledge obtained from prior survey data that female athletes report embarrassment, fear, anxiety and frustration as a consequence of PF disorders [ 20 ]. Many of the same negative emotions were also reported by participants within our study and the basis for experiencing these emotions described.…”
Section: Discussionmentioning
confidence: 98%
“…Self-disclosure of PF symptoms by female athletes is uncommon; less than 10% have ever told a health professional [ 16 – 19 ]. A recent systematic review of quantitative data found that elite female athletes employed coping strategies such as wearing pads, restricting fluids and frequent voiding to manage symptoms of UI [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is acknowledged that the reported prevalence figures for PFD show a large range throughout the literature due to varying case definitions, recruited populations, and study methodologies (53). The prevalence of urinary incontinence in athletes is often quantified using general, but validated questionnaires, such as the International Consultation on Incontinence Questionnaire Urinary Incontinence Short Form (54,55) and the Incontinence Severity Index (56). However, more recently sport-specific questions about leaking urine have been used (57,58).…”
Section: Prevalence Of Pfd In the General Population And In Athletesmentioning
confidence: 99%
“…For athletes, the sport itself is a modifiable risk factor. Female athletes report competition, training, and physical activity as the most significant triggers for their symptoms of PFD, followed by specific movements during their sport (54), such as impact-related activities ( e.g. , running, jumping) and strenuous activities ( e.g.…”
Section: The Dysfunctional Pelvic Floormentioning
confidence: 99%
See 1 more Smart Citation